Analisis Penerapan Pajak Penghasilan Pasal 23 Atas Jasa pada PT. Store Send E-Logistic Indonesia - Wahyu Widjayanti; Ayu Andrianie; Lince Afri Yenny; Dyah Palupi (Universitas 45 Surabaya, 2024)
This research was conducted at PT. Store Send E-Logistic Indonesia is a service company that provides comprehensive e-logistics solutions, starting from product management services in warehouses, online store management to the product delivery process to customers. The aim of this research is to determine and analyze the suitability of the application of PPh Article 23 in connection with the use of services at PT. Store Send E-Logistics Indonesia. The method used in this research is descriptive qualitative with primary data where direct observations and interviews were carried out with companies directly involved in managing PPh Article 23. The results of this research show that the company has carried out its Withholding, Deposit and Reporting obligations in accordance with tax regulations. especially law number 36 of 2008, although there were several errors caused by internal company parties.